Application of Activated Carbon and Natural Zeolite for Phosphate Removal from Laundry Wastewater - Tuty Emilia Agustina (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
The number of laundry industry has been increasing rapidly which influences the amount of detergent usage in the washing process. Generally the laundry industries dump their wastewater directly to environment without any treatment. Phosphate contained in detergent shall accumulate in the environment then finally would cause eutrofication where the water body becomes rich of dissolved nutrient which effects the dissolved oxygen contained in water body. One of wastewater treatment methods is adsorption. Two different kinds of adsorbents were applied in this investigation namely activated carbon and natural zeolite. Synthetic laundry wastewater was used in order to control the phosphate concentration. The objective of this experiment was to study the removal of phosphate concentration of each adsorbent filled in adsorption column by using circulation method. The column has 1 inch of diameter, 50 cm of height, and 50 ml/minute of flowrate. The concentration of phosphate was varied between 2-8 mg/l whereas the adsorbent height in the column was varied between the ranges of 10-40 cm. The size of both adsorbents was 10 mesh. It was found that the natural zeolite was superior to remove the phosphate compared to activated carbon. The highest phosphate removal of 90% was obtained by using 40 cm of natural zeolite height in the adsorption column when make use the phosphate concentration of 2 mg/l.